The Influence of Financial Literacy, Locus Of Control and Lifestyle on Cashless Society Behavior of Gen Z in Pontianak City - Syifa Azizah; Heni Safitri; Dedi Hariyanto (IECON: International Economics and Business Conference, 2025)
The purpose of this study is to investigate the impact of financial literacy, locus of control, and lifestyle on the cashless society behavior of Generation Z in Pontianak City.  This study employs quantitative methodologies.  Pontianak City's Generation Z population was researched.  The study sample was chosen using a purposive sampling method, in which the sample was chosen based on certain characteristics requested by the researcher.  This survey had a total of 100 respondents.  The outcomes of the study suggest that financial literacy has a positive and significant influence on cashless society behavior.  On the other hand, locus of control has a negative and minor influence on cashless society behavior.  And lifestyle has a favorable and important influence on cashless society behavior.